2020
DOI: 10.1039/d0ra04680a
|View full text |Cite
|
Sign up to set email alerts
|

Versatile vapor phase deposition approach to cesium tin bromide materials CsSnBr3, CsSn2Br5 and Cs2SnBr6

Abstract: We report on the application of RF-magnetron sputtering to deposit, by using a single type of target, three different materials in the form of thin films within the Cs–Sn–Br compositional range, namely, CsSnBr3, CsSn2Br5 and Cs2SnBr6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…To date, no vapor phase approaches have been used to prepare Cs 3 Bi 2 (I 1– x Br x ) 9 films. In addition, RF-magnetron sputtering has scarcely been used for perovskite films notwithstanding its huge potential for scale-up, providing stoichiometry control, good morphology, and high crystallinity and quality of deposited films, as we demonstrated recently. , Together with the structural and optical property characterization of the deposited films we report a significant photocatalytic activity in organic pollutant degradation combined with excellent water stability of the prepared materials. In the following, we start discussing the two end-members of the solid solution, namely Cs 3 Bi 2 Br 9 and Cs 3 Bi 2 I 9 , and then moving to the investigation of the mixed compositions.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…To date, no vapor phase approaches have been used to prepare Cs 3 Bi 2 (I 1– x Br x ) 9 films. In addition, RF-magnetron sputtering has scarcely been used for perovskite films notwithstanding its huge potential for scale-up, providing stoichiometry control, good morphology, and high crystallinity and quality of deposited films, as we demonstrated recently. , Together with the structural and optical property characterization of the deposited films we report a significant photocatalytic activity in organic pollutant degradation combined with excellent water stability of the prepared materials. In the following, we start discussing the two end-members of the solid solution, namely Cs 3 Bi 2 Br 9 and Cs 3 Bi 2 I 9 , and then moving to the investigation of the mixed compositions.…”
Section: Introductionmentioning
confidence: 65%
“…To conclude, this paper demonstrates the efficiency of sputtering in preparing thin films of all-inorganic lead-free Bi-based perovskites which are of huge interest for the wide community of photovoltaics, optoelectronics, and more recently, photocatalysis. As we already demonstrated for other metal halide perovskites, sputtering seems to be a method to be extended to several systems to further boost the scale-up of perovskite-based technology, in particular for all-inorganic systems which face relevant problems in wet-chemistry depositions. …”
Section: Discussionmentioning
confidence: 98%
“… a true m normalx 0em true̅ values are computed from the harmonic mean over directions and light/heavy bands for the effective masses. Values of >1 are given to one decimal place. b Experimental band gap values taken from refs , , , and for Cs 2 SnCl 6 , refs , , , and for Cs 2 SnBr 6 , refs , , , , , , and for Cs 2 SnI 6 , refs and for Cs 2 TiCl 6 , refs , , , , , , , and for Cs 2 TiBr 6 , and refs and for Cs 2 TiI 6 . …”
mentioning
confidence: 99%
“… b Experimental band gap values taken from refs , , , and for Cs 2 SnCl 6 , refs , , , and for Cs 2 SnBr 6 , refs , , , , , , and for Cs 2 SnI 6 , refs and for Cs 2 TiCl 6 , refs , , , , , , , and for Cs 2 TiBr 6 , and refs and for Cs 2 TiI 6 . …”
mentioning
confidence: 99%
“…PSCs device was coated with an additional 30 mol% SnF 2 on the MASnIBr 2 perovskite layer, the cell has PCE of 3.7%, a higher quality perovskite film, and less carrier recombination. Hartmann et al, 85 studied the effect of SnF 2 on CsSnBr 3, they confirmed that 20 mol% SnF 2 suppressed the oxidation of Sn 2+ . Most tin‐based PSCs now employ SnF 2 to attain excellent photovoltaic performance 75,85 …”
Section: Discussionmentioning
confidence: 90%